m6A RNA Methylation Regulators Participate in the Malignant Progression and Have Clinical Prognostic Value in Lung Adenocarcinoma - Li, Fangwei; Wang, Hong; Huang, Huirong; Zhang, Li; Wang, Dan; Wan, Yixin (Frontiers in Genetics, 2020)
Abnormal methylation of N6 adenosine (m6A) in RNA plays a crucial role in the pathogenesis of many types of tumors. However, little is known about m6A RNA methylation in lung adenocarcinoma. This study aimed to identify the value of m6A RNA methylation regulators in the malignant progression and clinical prognosis of lung adenocarcinoma. The RNA-seq transcriptome data and corresponding clinical information of lung adenocarcinoma were downloaded from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database. Then the identification of differentially expressed m6A RNA methylation regulators between cancer samples and normal control samples, different subgroups by consensus expression of these regulators and the prognostic signature were achieved using R software with multiple corresponding packages. The results showed that the expression levels of HNRNPC, YTHDF1, KIAA1429, RBM15, YTHDF2 and METTL3 in cancer group were significantly up-regulated (P < 0.05), while expression levels of FTO, ZC3H13, METTL14, YTHDC1 and WTAP in cancer group were significantly down-regulated (P < 0.05) compared with control group. Two subgroups identified by consensus expression of these regulators were closely related to the clinicopathological features, clinical outcomes and malignancy of lung adenocarcinoma. In addition, a 3-gene risk signature including KIAA1429, RBM15 and HNRNPC was constructed and the lung adenocarcinoma patients in TCGA database were divided into high-risk group and low-risk group based on the median risk score. In conclusion, the prognostic signature-based risk score calculated according to the expression levels of KIAA1429, RBM15 and HNRNPC, was not only strongly associated with clinical outcomes and clinicopathological features, but also an independent prognostic factor in lung adenocarcinoma.